Human Governance Index of Manufacturing Sector of Shariah Compliant Companies in Malaysia: A Preliminary Analysis - Dato' Hasnah Hj Haron; Nurul Nazlia Jamil; Nathasa Mazna Ramli; Sumaiyah Abd Aziz; Syahnaz Sulaiman; Idris Gautama; Anderes Gui; Synthia Atas Sari; Nurul ‘Athirah Rosli; Nurul Kamarina Kamarudin (Penerbit UMP, 2024)
Indexed by MyCite